2023
DOI: 10.7554/elife.81173
|View full text |Cite
|
Sign up to set email alerts
|

Shared enhancer gene regulatory networks between wound and oncogenic programs

Abstract: Wound response programs are often activated during neoplastic growth in tumors. In both wound repair and tumor growth, cells respond to acute stress and balance the activation of multiple programs including apoptosis, proliferation, and cell migration. Central to those responses are the activation of the JNK/MAPK and JAK/STAT signaling pathways. Yet, to what extent these signaling cascades interact at the cis-regulatory level, and how they orchestrate different regulatory and phenotypic responses is still uncl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 111 publications
2
10
0
Order By: Relevance
“…This data confirmed phtm induction in wound cells and further refined this expression to 'beta' wound cells (Fig. S4A-B, H) (as defined in Floc'hlay et al, 2023). Expression of sro (shroud), a Halloween gene that acts upstream of phtm in the Ec synthesis pathway, is detected by scSeq throughout the disc independent of injury (Fig.…”
Section: The Regeneration Genes Upd3 and Ets21c Respond To Ecsupporting
confidence: 78%
See 1 more Smart Citation
“…This data confirmed phtm induction in wound cells and further refined this expression to 'beta' wound cells (Fig. S4A-B, H) (as defined in Floc'hlay et al, 2023). Expression of sro (shroud), a Halloween gene that acts upstream of phtm in the Ec synthesis pathway, is detected by scSeq throughout the disc independent of injury (Fig.…”
Section: The Regeneration Genes Upd3 and Ets21c Respond To Ecsupporting
confidence: 78%
“…Based on a prior RNA-seq study that identified phtm mRNA among a group of injury-induced transcripts in sorted cells from rn>rpr ts blastemas (Khan et al, 2017), we reanalyzed a public single-cell RNA sequencing (scSeq) data derived from injured (rn>egr ts system) and uninjured larval wing discs (Floc'hlay et al, 2023). This data confirmed phtm induction in wound cells and further refined this expression to 'beta' wound cells (Fig.…”
Section: The Regeneration Genes Upd3 and Ets21c Respond To Ecmentioning
confidence: 69%
“…Expression of egr induces upd1-3 , the pro-mitogenic cytokines for the JAK/STAT pathway ( S2 Fig ; [ 72 ] ) [ 18 , 26 , 48 , 50 ]. Yet, high JNK-signaling cells in egr- expressing discs that up-regulated a transcriptional upd3 reporter did not exhibit JAK/STAT activity, as assessed by the 10xStat92E-dGFP reporter ( Fig 3A–3G ) [ 73 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…At the level of cell behaviors, JNK/AP-1 and JAK/STAT generate mutually exclusive responses. JNK/AP-1 signaling supports wound behaviors like tissue sealing [ 22 , 23 , 81 ], cell fusion [ 12 ], establishment of paracrine signaling [ 72 ], and, importantly, an apoptosis-resistant state that depends on a G2 cell cycle arrest [ 29 ]. In contrast, JAK/STAT signaling supports compensatory proliferation, potentially via up-regulation of G1-S cyclins such as CycD or CycE [ 142 , 143 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation